Nn PEMBELAJARAN EKSTRAKULIKULER MUSIK GAMBUS DI MA NEGERI 4 JOMBANG - Dyah Ilmillah; Tomy Agung Sugito (Universitas Negeri Surabaya, 2024)
This study was motivated by the sustainability of the gambus music extracurricular program at MA Negeri 4 Jombang, which has been consistently implemented despite the demanding schedules of students as Islamic boarding school (santri) members. This condition reflects a learning process that accommodates students' time constraints while supporting the development of their artistic potential. Therefore, this study aims to describe the planning and implementation of the gambus music extracurricular learning program and to analyze its impact on students' interest, attitudes, and discipline in artistic activities. This study employed a qualitative approach with a descriptive research design. The data were collected through observations, interviews, and documentation. The research participants consisted of the extracurricular coordinator, the instructor, and students participating in the gambus music extracurricular program at MA Negeri 4 Jombang. Furthermore, the data were analyzed through the processes of data collection, data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation techniques. The findings indicate that the learning program was systematically planned by establishing learning objectives, selecting appropriate instructional materials, applying demonstration and direct practice methods, utilizing gambus musical instruments as learning media, and conducting continuous evaluations based on students' learning progress. The learning implementation consisted of introductory, core, and closing activities, with an emphasis on collaborative musical practice. Although the program encountered several challenges, including limited facilities, differences in students' abilities, and the demanding schedules of santri, the extracurricular activities were implemented effectively. Moreover, participation in the gambus music extracurricular program positively contributed to enhancing students' interest in the arts, fostering responsibility and teamwork, and strengthening their discipline in participating in extracurricular activities.